2021
DOI: 10.3349/ymj.2021.62.4.325
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Long Noncoding RNA SNHG15 Ameliorates Hypoxia/Ischemia-Induced Neuronal Damage by Regulating miR-302a-3p/STAT1/NF-κB Axis

Abstract: Purpose Ischemic brain injury results in high mortality and serious neurologic morbidity. Here, we explored the role of SNHG15 in modulating neuronal damage and microglial inflammation after ischemia stroke. Materials and Methods The hypoxia/ischemia models were induced by middle cerebral artery occlusion in mice and oxygen-glucose deprivation/reoxygenation (OGD/R) in vitro. Quantitative real-time PCR (qRT-PCR) and Western blot were conducted to determine the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…In addition, SNHG15-silencing significantly attenuated LPS-induced apoptosis and proliferation inhibition of HUVECs. A number of studies have consistently shown that down-regulation of SNHG15 can improve ischemic/hypoxia-induced neuronal injury and microglial inflammation, and inhibit the progression of ischemic stroke (18,19), which is consistent with the protective effect of SNHG15 silencing in this study. These studies suggest that SNHG15 is related to LPS-induced vascular endothelial cell injury, and silencing SNHG15 may be an important strategy based on vascular endothelial cell inhibition of sepsis progression.…”
Section: Effects Of Mir-362-3p On Lps-induced Expression and Oxidativ...supporting
confidence: 91%
“…In addition, SNHG15-silencing significantly attenuated LPS-induced apoptosis and proliferation inhibition of HUVECs. A number of studies have consistently shown that down-regulation of SNHG15 can improve ischemic/hypoxia-induced neuronal injury and microglial inflammation, and inhibit the progression of ischemic stroke (18,19), which is consistent with the protective effect of SNHG15 silencing in this study. These studies suggest that SNHG15 is related to LPS-induced vascular endothelial cell injury, and silencing SNHG15 may be an important strategy based on vascular endothelial cell inhibition of sepsis progression.…”
Section: Effects Of Mir-362-3p On Lps-induced Expression and Oxidativ...supporting
confidence: 91%
“…SNHG4 can promote M2 polarization in microglia by sponging miR-449c-5p and thereby activating the signal transducer and activator of transcription 6 (STAT6) signaling pathway ( Zhang et al, 2020 ). In contrast, SNHG15 promotes STAT1 and its NF-κB expression by sponging miR-302a-3p, contributing to the M1 polarization of microglia ( Hu et al, 2021 ). In addition, the remaining sponging combinations were lncRNA TUG1/miR-145a-5p promoting M1 polarization, lncRNA HOTAIR/miR-136-5 promoting AKT2 expression and thus upregulating NF-κB for M1 polarization, lncRNA parent expression gene 3 and sponged miR-7a-5p together upregulating nod-like receptor protein 3 (NLRP3) to promote M1 polarization ( Duan et al, 2018 ; Wang et al, 2019 ; Meng et al, 2021 ).…”
Section: Lncrna/microrna Axis and Microglia Polarizationmentioning
confidence: 99%
“…The role of NF-κB pathway in ischemic stroke has been well described. In a MCAO and in vitro oxygenated glucose deprivation/reoxygenation-induced hypoxia/ischemia, SNHG15 sponges miR-302a-3p thereby promoting STAT1 and NF-κB expression and activating microglia involved in the development of ischemic brain injury ( Hu et al, 2021 ). In ex vivo ischemic stroke experiments, lncRNA-1810034E14Rik may exert anti-inflammatory effects by inhibiting the NF-κB pathway and suppressing microglia activation and p65 hyperphosphorylation, with implications for stroke treatment ( Zhang et al, 2019e ).…”
Section: Current Status Of Research On the Relationship Between Lncrn...mentioning
confidence: 99%
“…116 LncRNA SNHG15 increases neuronal damage and microglial inflammation by sponging miR-302a-3p as a competitive endogenous RNA, while this miRNA targets STAT1 and negatively regulates the NF-κB pathway. 88 In addition, Kuai et al 89…”
Section: Lncrna-microrna-mrna Axis Is the Key Player In Regulating Inflammation Upon Ischemic Strokementioning
confidence: 99%
“… 116 LncRNA SNHG15 increases neuronal damage and microglial inflammation by sponging miR-302a-3p as a competitive endogenous RNA, while this miRNA targets STAT1 and negatively regulates the NF-κB pathway. 88 In addition, Kuai et al 89 and Tian et al 11 revealed that lncRNAs Snhg8 and THRIL regulate inflammation and microglia activation via SIRT1 and neuropilin-1 (NRP1), respectively, by regulating the NF-κB pathway. Thus, lncRNAs might contribute to regulating neuroinflammation and microglia activation by THRIL, NRP1, and STAT1, which further regulate the NF-κB pathway.…”
Section: Significant Role Of Long Noncoding Rnas In Cerebral Ischemiamentioning
confidence: 99%